2013
DOI: 10.1007/s00296-013-2833-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an algorithm for identifying rheumatoid arthritis in the Korean National Health Insurance claims database

Abstract: This study aimed to develop an identification algorithm for validating the International Classification of Diseases-Tenth diagnostic codes for rheumatoid arthritis (RA) in the Korean National Health Insurance (NHI) claims database. An individual copayment beneficiaries program for rare and intractable diseases, including seropositive RA (M05), began in South Korea in July 2009. Patients registered in this system pay only 10 % of their total medical costs, but registration requires an official report from a doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 11 publications
4
62
0
Order By: Relevance
“…Nevertheless, daily intake of nutrients in our study is largely comparable with previous studies [3]. In terms of prevalence of RA, that in K-NHANES was slightly lower than expected (0.26%) compared with previous reports [30]. Lastly, we were unable to look into disease duration or activity of RA, and concomitant medication especially glucocorticoids, taken by RA subjects in K-NHANES.…”
Section: Discussionsupporting
confidence: 65%
“…Nevertheless, daily intake of nutrients in our study is largely comparable with previous studies [3]. In terms of prevalence of RA, that in K-NHANES was slightly lower than expected (0.26%) compared with previous reports [30]. Lastly, we were unable to look into disease duration or activity of RA, and concomitant medication especially glucocorticoids, taken by RA subjects in K-NHANES.…”
Section: Discussionsupporting
confidence: 65%
“…The International Classification of Diseases and Injuries 10th Revision (ICD‐10) code was used to record diagnoses in this database. It has been shown that this database provides reliable estimates of the real prevalence of certain diseases in Korea …”
Section: Methodsmentioning
confidence: 99%
“…We suggest that further work be done to derive and validate accurate methods that use population‐based health administrative data to identify patients with CRS. This has been used to identify other diseases, for example rheumatoid arthritis, in large administrative databases with good accuracy . Improvements in natural language processing (NLP) technology could help identify key terms in CT reports, OR dictation summaries, and patient charts to improve efficiency and accuracy in developing CRS algorithms …”
Section: Discussionmentioning
confidence: 99%